An IoT-Based Weather Monitoring and Flood Early Warning System - Sandi Setyansah; Brilliant Elyon Prasetyo; Moch Diva Firmansyah; Harianto .; Ira Puspasari (Universitas Multi Data Palembang, 2026)
This study presents the design and implementation of an integrated Internet of Things based weather monitoring and flood early warning system. The system simultaneously monitors temperature, humidity, rainfall intensity, and water level in real time using a NodeMCU ESP8266 microcontroller integrated with DHT11, rain, and ultrasonic sensors. Experimental results show that the system successfully classifies environmental conditions, where temperatures below 25 °C and humidity levels above 80% indicate heavy rainfall, while rainfall sensor values range between 2000–3000 ADC units. Water-level testing demonstrates that the early warning buzzer is activated when the water level reaches a minimum threshold of 5 cm and remains active below 10 cm, indicating potential flood conditions. Sensor data are transmitted reliably in real time via the MQTT protocol and visualized on a monitoring dashboard without significant delay. These results confirm that the proposed system provides accurate environmental monitoring and effective early flood warning, offering a low-cost and practical solution for flood disaster preparedness.